Hands-On Machine Learning with TensorFlow. js : A Guide to Building ML Applications Integrated with Web Technology Using the TensorFlow. js Library /: A Guide to Building ML Applications Integrated with Web Technology Using the TensorFlow. js Library. (2019) - Sasaki, Kai
No abstract available